Faktor-Faktor Yang Berhubungan Dengan Kejadian Preeklamsi Pada Ibu Hamil Di Rsud Kota Depok - Indah Sri Wahyuni (Politeknik Karya Husada, 2022)
Background: Preeclampsia/eclampsia is a complication of pregnancy and childbirth characterized by increased blood pressure, proteinuria and edema. Objective: to determine the factors associated with the incidence of preeclampsia in pregnant women at the Depok City Hospital. Methods: this research is descriptive using medical record data at RSUD Kota Depok with a cross sectional design. Results: The study showed that pregnant women who experienced PEB were (59.2%), factors related to pre-eclampsia were age, parity, history of hypertension with p value <0.05 Conclusion: pregnant women should have regular check-ups so that it can be detected regularly fast in handling the incidence of pre-eclampsia Keywords: Pregnant women, pre-eclampsia, eclampsia.